Automata and Pygmalions in the Romantic Imagery: Uncanny and Ambivalence (ENTHYMEMA, 2024)
This study tackles the representation of automata in Romanticism, with a specific focus on the concepts of 'uncanny' and 'ambivalence.' The reflection includes the themes of the mirror, the ideal image of the self (Ideal Ich), and the female figure, from a perspective that takes into consideration traces of the Pygmalion and Promethean myths in the Romantic imagery. The first paragraph traces an overview of the forms of the automaton over time, starting from the classical age; it is followed by a brief framing of the dominant historical and philosophical categories in Romanticism, the identification of the Fantastic as a literary mode and the comparative analysis of two case studies: E.T.A. Hoffmann’s Der Sandmann (1816) and August Villiers de L’Isle-Adam’s L’Ève future (1886). The comparison aims at highlighting constants and variants in the meanings embodied by the automaton in two works covering a time span that goes from the ascent of Romanticism with Hoffmann to its later expression with Villiers.
Keywords: Automa; Uncanny; Pygmalionic Myth; E.T.A. Hoffmann; Auguste de Villiers de l'Isle-Adam